Use the identity (x + a)(x + b) = x2 + (a + b)x + ab to find the following products.
(i) (x + 3) (x + 7)
Use the identity (x + a)(x + b) = x2 + (a + b)x + ab to find the following products.
(4x + 5) (4x + 1)
Use the identity (x + a)(x + b) = x2 + (a + b)x + ab to find the following products.
(4x - 5) (4x - 1)
Use the identity (x + a)(x + b) = x2 + (a + b)x + ab to find the following products.
(4x + 5) (4x - 1)
Use the identity (x + a)(x + b) = x2 + (a + b)x + ab to find the following products.
(2x +5y) (2x + 3y)
Use the identity (x + a)(x + b) = x2 + (a + b)x + ab to find the following products.
(2a2 + 9) (2a2 + 5)
Use the identity (x + a)(x + b) = x2 + (a + b)x + ab to find the following products.
(xyz - 4) (xyz - 2)
Find the following squares by using the identities.
(b - 7)2
(b - 7)2
Using (a - b)2 = a2 + 2ab + b2 , we have
(b - 7)2 = (b)2 - 2(b)(7) + (7)2
= b2 - 14b + 49